2020
DOI: 10.4103/psychiatry.indianjpsychiatry_523_20
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep pattern and sleep quality during COVID-19 lockdown

Abstract: Introduction: To mitigate the spread of the pandemic coronavirus infection (COVID-19), governments across the world have adopted “lockdowns” which have confined many individuals to their homes. This disrupts normal life routines, elements of which are important circadian cues. The pandemic is also associated with new stressors, altered roles, and uncertainties about health and economic security, which are also likely to affect sleep. The current study is an online survey of sleep experience, routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
148
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(168 citation statements)
references
References 28 publications
(45 reference statements)
14
148
1
5
Order By: Relevance
“…There was no significant correlation between the factor insomnia and the three factors of perceived stress. This is consistent with Gupta et al 31 who found no significant difference in perceived stress among three different groups with varying levels of nighttime sleep duration after lockdown due to COVID19. It may be noted that insomnia can be caused by several other factors apart from stress.…”
Section: Discussionsupporting
confidence: 91%
“…There was no significant correlation between the factor insomnia and the three factors of perceived stress. This is consistent with Gupta et al 31 who found no significant difference in perceived stress among three different groups with varying levels of nighttime sleep duration after lockdown due to COVID19. It may be noted that insomnia can be caused by several other factors apart from stress.…”
Section: Discussionsupporting
confidence: 91%
“…, 11. , 17 and changes in sleep patterns 14 , 15 are common. The current findings extend those of these regional studies to show substantial changes in sleep behavior in a global general population sample.…”
Section: Discussionmentioning
confidence: 99%
“…, 13. and shifts in sleep patterns 14 , 15 in frontline health care workers and the general community. Also, there is preliminary evidence that depression and anxiety levels during the COVID-19 pandemic are elevated and potentially associated with poorer sleep quality (for a review see: 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the same survey, 49% of respondents reported feeling more anxious and depressed as a direct result of COVID-19. Gupta et al (2020) examined changes in sleep pattern and sleep quality during COVID-19 using a questionnaire distributed via social media platforms. Compared to the pre-lockdown period, all occupational groups (except health professionals) evidenced a shift to a later bedtime, a reduction in night-time sleep, an increase in day-time napping, and a deterioration in sleep quality.…”
Section: Introductionmentioning
confidence: 99%